Kemiskinan dan Migrasi: Analisis Data SAKERTI 2000 dan 2007 - Nabila, Aulia; Pardede, Elda L. (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
This paper aims to analyze the effect of poverty on migration by using the IFLS 2000 and 2007 data. The results of binary and multinomial logistic regressions on all adults, adults in urban areas, and adults in rural areas show that the poor are less likely to migrate than the non-poor except for the case of urban to urban migration, where the poor are more likely to migrate than the non-poor. The results for other economic characteristics such as total value of assets and land ownership for farming consistently show that better economic conditions lower the probability to migrate.